Mobilizing Japanese youth the Cold War and the making of the sixties generation - Gerteis, Christopher, 1968- (Ithaca [New York] Cornell University Press, 2021)
"Examines the forces that shaped the political consciousness of Japanese youth who chose to engage in political violence during the 1960s and 1970s. The book argues in part that the intertwined political rhetoric of the far left and far right precipitated further levels of social alienation that helped to define the political consciousness of the 'Sixties Generation' well into the twenty-first century"--
Unions, Youth and the Cold War -- The Rise And Fall of the Japanese Red Army -- Political Alienation and the Sixties Generation -- Cold War Warriors -- Motorboat Gambling and Morals Education
Includes bibliographical references and index
Description based on online resource; title from digital title page (viewed on June 28, 2021).
In English.
JSTOR
Keywords: Youth -- Political activity -- Japan -- History -- 20th century; Radicalism -- Japan -- History -- 20th century; Political violence -- Japan -- History -- 20th century; Political alienation -- Japan -- History -- 20th century; Japan -- Politics and government -- 1945-; Jeunesse -- Activité politique -- Japon -- Histoire -- 20e siècle.; Radicalisme -- Japon -- Histoire -- 20e siècle.; Violence politique -- Japon -- Histoire -- 20e siècle.; Aliénation politique -- Japon -- Histoire -- 20e siècle.; Japon -- Politique et gouvernement -- 1945-; HISTORY / Asia / Japan; Political alienation; Political violence; Politics and government; Radicalism; Youth -- Political activity; Japan; Since 1900; youth politics, The Japanese Red Army, Sasakawa Ryōichi, Kodama Yoshio, Shigenobu Fusako, Radical Youth, US-Japan Security Treaty, Vietnam War and Japan, Sixties Generation in Japan; Electronic books; History